Plasma Parameters From Quasi‐Thermal Noise Observed by Parker Solar Probe: A New Model for the Antenna Response. Issue 4 (31st March 2022) - Martinović, Mihailo M.; Ðorđević, Antonije R.; Klein, Kristopher G.; Maksimović, Milan; Issautier, Karine; Liu, Mingzhe; Pulupa, Marc; Bale, Stuart D.; Halekas, Jasper S.; McManus, Michael D.
Abstract: Quasi‐Thermal Noise (QTN) spectroscopy is a reliable diagnostic routinely used for measuring electron density and temperature in space plasmas. The observed spectrum depends on both antenna geometry and plasma kinetic properties. Parker solar probe (PSP), launched in 2018, is equipped with an antenna system consisting of two linear dipoles with a significant gap between the antenna arms. Such a configuration, not utilized on previous missions, cannot be completely described by current models of the antenna response function. In this work, we calculate the current distribution and the corresponding response function for the PSP antenna geometry, and use these results to generate synthetic QTN spectra. Applying this model to the Encounter 7 observations from PSP provides accurate estimations of electron density and temperature, which are in very good agreement with particle analyzer measurements. Plain Language Summary: Parker solar probe (PSP) is a NASA mission that is travelling much closer to the Sun than any previous spacecraft. A primary consequence of this specific trajectory are multiple adaptations in the design of instruments (radio instruments, magnetometers, particle detectors etc.) and their complex accommodations on the spacecraft. This article investigates effects of the specific PSP radio antenna geometry to high‐frequency electric field observations. We apply Quasi‐Thermal Noise Spectroscopy, a well established method for determining plasma density and temperature, to PSP radio observations using dipole antennas, and validate the results by comparing the parameter values from radio observations to the ones obtained by particle analyzers onboard PSP. Key Points: We model the antenna response for the unique geometry of linear dipole antenna containing a gap between arms This antenna response is used to improve plasma parameters determination from the observed quasi‐thermal noise spectrum The proposed model yields derived electron parameters consistent with those from the SWEAP/SPAN instrument suite onboard Parker solar probe